1982
DOI: 10.1002/ajh.2830130310
|View full text |Cite
|
Sign up to set email alerts
|

Studies of a patient with recurring thrombotic thrombocytopenic purpura

Abstract: A young woman with recurring bouts of thrombotic thrombocytopenic purpura presented an opportunity to study a single patient serially and in depth. This patient underwent 12 remissions in response to fresh frozen plasma, and as little as 250 ml of plasma or plasma from which cryoprecipitate had been extracted with efficacious. Neither the Lian factor nor alterations in either cold-insoluble globulin or protein C could be demonstrated. Evidence in support of the concept of "exhausted" platelets was generated, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Our experience with one patient (Case 4), as well as that of others [86,87,91,93], indicates that plasma infusion alone may be beneficial. The choice of treatment should, of course, be determined by the severity of the clinical manifestations, as PE is an invasive and not entirely benign procedure.…”
Section: Discussionmentioning
confidence: 72%
“…Our experience with one patient (Case 4), as well as that of others [86,87,91,93], indicates that plasma infusion alone may be beneficial. The choice of treatment should, of course, be determined by the severity of the clinical manifestations, as PE is an invasive and not entirely benign procedure.…”
Section: Discussionmentioning
confidence: 72%
“…Long-lasting remissions after splenectomy in patients with relapsing TTP or chronic TTP have been observed by others in small series and case reports (Table 3) [,-21, 24-26]. TTP is rare in patients in whom the spleen had been removed [7,17,35]. Relapses after splenectomy have been described, in most of the patients after long disease-free intervals [14,19,24].…”
Section: Splenectomy In Relapsing Ttpmentioning
confidence: 73%
“…Further, the use of a high-dose of IgG would be inappropriate to control TTP during pregnancy due to its high cost and the uncertainty of its effect. It also has been reported [15] that the cryosupernatant fraction of plasma is clinically effective against TTP. Moake et al [ 161 have reported that the cryosupernatant fraction is able to control the metabolism of the unusually large vWf multimers.…”
Section: Discussionmentioning
confidence: 94%